Identification of mecA Gene in Methicillin-Resistant Staphylococcus aureus (MRSA) Using Molecular Method from Clinically Isolated Samples in Babylon Province, Iraq - Enas k. Alkhazraji; Ameer Abood Karim Al-Rammahi (Universitas Muhammadiyah Sidoarjo, 2026)
General Background: Methicillin-resistant Staphylococcus aureus (MRSA) is a significant cause of hospital- and community-acquired infections due to its antibiotic resistance. Specific Background: Molecular diagnosis using polymerase chain reaction (PCR) is widely used to identify MRSA strains carrying the mecA gene. Knowledge Gap: Data on mecA-positive MRSA isolates and antibiotic resistance patterns in Babylon Governorate, Iraq, remain limited. Aims: This study aimed to isolate and identify MRSA from clinical samples and evaluate antibiotic susceptibility patterns. Results: Among 100 clinical samples, 60% were positive for Staphylococcus aureus, and 58.3% of the isolates were confirmed as MRSA by mecA gene detection. Wound and pus samples showed the highest MRSA prevalence. The isolates exhibited high resistance to penicillin, methicillin, and erythromycin, while vancomycin and linezolid showed high sensitivity rates. Novelty: The study combines molecular detection of mecA-positive MRSA with antibiotic susceptibility profiling in clinical isolates from Babylon hospitals. Implications: The findings support the use of PCR-based diagnosis, antibiotic stewardship, and infection control programs to reduce the spread of resistant bacterial strains. Highlights: • Molecular PCR analysis confirmed mecA-positive MRSA strains in more than half of the Staphylococcus aureus isolates.• Wound and pus specimens represented the primary clinical source of resistant bacterial isolates.• Vancomycin and linezolid demonstrated high susceptibility rates against multidrug-resistant strains. Keywords: Methicillin Resistant Staphylococcus Aureus, mecA Gene, Polymerase Chain Reaction, Antibiotic Resistance; Clinical Isolates,